Pelanggaran Implementasi AMDAL Dan Dampaknya Terhadap Pencemaran Air di Pulau Jawa: AMDAL Implementation Violations and Their Impact on Water Pollution in Java Island - Nabila Najwa Arifiani; Wijayono Hadi Sukrisno; Syafran Sofyan (Universitas Semarang, 2025)
This study examines the implementation of legal protection against water pollution caused by violations of the Environmental Impact Assessment (AMDAL) requirements within the environmental licensing process in Java. The urgency of this research arises from the increasing degradation of water quality resulting from business actors’ non-compliance with ecological management commitments, weak governmental oversight, and inadequate enforcement of environmental regulations. Using a socio-legal research method with a descriptive-analytical approach, data were collected through field observations, interviews with governmental officials and affected communities, and a review of statutory regulations and AMDAL documents. The findings reveal that AMDAL preparation and implementation are frequently treated as mere administrative formalities, undermining their preventive function in environmental protection. Violations of AMDAL obligations significantly contribute to water pollution in industrial regions across Java. The novelty of this research lies in its comprehensive mapping of factors contributing to AMDAL implementation violations, their legal implications, and the proposed framework for strengthening AMDAL as a substantive environmental protection instrument. Penelitian ini menganalisis pelaksanaan perlindungan hukum terhadap pencemaran air yang timbul akibat pelanggaran implementasi Analisis Mengenai Dampak Lingkungan (AMDAL) dalam proses perizinan lingkungan di Pulau Jawa. Urgensi penelitian muncul dari meningkatnya pencemaran air yang bersumber dari ketidakpatuhan pelaku usaha terhadap komitmen pengelolaan lingkungan, lemahnya pengawasan pemerintah, serta ketidaktegasan penegakan hukum. Penelitian ini menggunakan metode yuridis sosiologis dengan pendekatan deskriptif-analitis melalui observasi lapangan, wawancara dengan aparat pemerintah dan masyarakat terdampak, serta kajian kepustakaan terhadap peraturan perundang-undangan dan dokumen AMDAL. Hasil penelitian menunjukkan bahwa penyusunan dan implementasi AMDAL seringkali diperlakukan sebagai formalitas administratif, sehingga tidak mampu berfungsi sebagai instrumen pencegahan pencemaran. Pelanggaran implementasi AMDAL terbukti menjadi faktor signifikan meningkatnya pencemaran air di beberapa daerah industri. Novelty penelitian ini terletak pada pemetaan komprehensif faktor penyebab pelanggaran implementasi AMDAL beserta analisis akibat hukumnya, serta rekomendasi penguatan instrumen AMDAL sebagai alat perlindungan lingkungan yang substantif.